2016
DOI: 10.1111/ijal.12128
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic complexity at multiple proficiency levels of L2 German speech

Abstract: Syntactic complexity, along with accuracy and fluency, has been proposed as an essential construct in the description of second language proficiency. This study examined three dimensions of complexity using oral data from learners of German at the intermediate, advanced, and superior proficiency levels. The data were examined for complexity by subordination, complexity by coordination, and phrasal complexity. The results showed that all three complexity measures showed different patterns of use as proficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
10
1
2
Order By: Relevance
“…Hirano () found that the ratio of dependent clauses to total clauses increased with proficiency level, but no relation could be established between the number of dependent clauses per clause and the proficiency level of the learners. Contrary to Hirano's results, Neary‐Sundquist () detected significant differences in complexity by subordination between the intermediate, advanced, and highly advanced L2 participants of the study.…”
Section: Studies On Measures Of Syntactic Complexity: Coordination Scontrasting
confidence: 76%
See 4 more Smart Citations
“…Hirano () found that the ratio of dependent clauses to total clauses increased with proficiency level, but no relation could be established between the number of dependent clauses per clause and the proficiency level of the learners. Contrary to Hirano's results, Neary‐Sundquist () detected significant differences in complexity by subordination between the intermediate, advanced, and highly advanced L2 participants of the study.…”
Section: Studies On Measures Of Syntactic Complexity: Coordination Scontrasting
confidence: 76%
“…Lu () and Ai and Lu (), instead, found no significant differences between L2 proficiency levels. In line with the latter findings, Neary‐Sundquist () found no significant differences in the rate of coordination between intermediate, advanced and highly advanced L2 learners. Despite this lack of significant differences between proficiency levels, the outcomes of the study by Neary‐Sundquist appeared to confirm the developmental “omega‐shaped” pattern suggested by Wolfe‐Quintero et al (), which is to say a decrease of coordination at higher proficiency levels in favour of subordination and, similarly, a decline of subordination in favour of phrasal complexity at the superior levels.…”
Section: Studies On Measures Of Syntactic Complexity: Coordination Smentioning
confidence: 57%
See 3 more Smart Citations